PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN LOYALITAS KARYAWAN TERHADAP PRESTASI KERJA KARYAWAN PADA KOPERASI DANU JAYA TABANAN - Prabudi, I Made; Suana, I Wayan (E-Jurnal Manajemen, 2015)
The purpose of this study was to determine the effect of transformational leadership and employee loyalty on employee performance at Koperasi Danu Jaya Tabanan. This study used a quantitative research by using surveys and questionnaires to 40 employees of Koperasi Danu Jaya Tabanan. The data analysis technique used is multiple linear regression analysis. Obtained findings that transformational leadership and significant positive effect on employee performance in Koperasi Danu Jaya Tabanan. Other results found that employee loyalty and a significant positive effect on employee performance in Koperasi Danu Jaya Tabanan. Furthermore, transformational leadership and employee loyalty simultaneously significant effect on employee performance in Koperasi Danu Jaya Tabanan.
Keywords: Kepemimpinan Transformasional; Loyalitas Karyawan; Prestasi Kerja